SDSS-IV MaNGA: The Effect of Stellar Mass and Halo Mass on the Assembly Histories of Satellite Galaxies - Grecco A. Oyarzún; Kevin Bundy; Kyle B. Westfall; Ivan Lacerna; Renbin Yan; J. R. Brownstein; Niv Drory; Richard R. Lane (The Astrophysical Journal, 2023)
We combine an unprecedented MaNGA sample of over 3000 passive galaxies in the stellar mass range 10 ^9 –10 ^12 M _⊙ with the Sloan Digital Sky Survey group catalog by Tinker to quantify how central and satellite formation, quantified by radial profiles in stellar age, [Fe/H], and [Mg/Fe], depends on the stellar mass of the galaxy ( M _* ) and the mass of the host halo ( M _h ). After controlling for M _* and M _h , the stacked spectra of centrals and satellites beyond the effective radius ( r _e ) show small, yet significant differences in multiple spectral features at the 1% level. According to spectral fitting with the code alf , a primary driver of these differences appears to be [Mg/Fe] variations, suggesting that stellar populations in the outskirts of satellites formed more rapidly than the outer populations of centrals. To probe the physical mechanisms that may be responsible for this signal, we examined how satellite stellar populations depend on M _h . We find that satellites in high- M _h halos show older stellar ages, lower [Fe/H], and higher [Mg/Fe] compared to satellites in low- M _h halos, especially for M _* = 10 ^9.5 –10 ^10.5 M _⊙ . These signals lend support to environmentally driven processes that quench satellite galaxies, although variations in the merger histories of central and satellite galaxies also emerge as a viable explanation.